127k views
2 votes
If g (x) is the inverse of f (x) and f (x) = 4 x + 12, what is g (x)

g (x) = 12 x + 4
g (x) = one-fourth x minus 12
g (x) = x minus 3
g (x) = one-fourth x minus

User Vijesh
by
5.7k points

2 Answers

4 votes
g(x)=1/4x-3 is what i got
User Nicosmik
by
5.8k points
6 votes

Answer:


g(x) = (1)/(4) x - 3

Explanation:

Since g(x) is the inverse of f (x) to find g(x) must first find f-¹(x)

To find f-¹(x) equate f(x) to y

That's

f(x) = y

y = 4x + 12

Next interchange the terms x becomes y and y becomes x

That's

x = 4y + 12

Next make y the subject

4y = x - 12

Divide both sides by 4


y = (1)/(4) x - 3

Therefore


g(x) = (1)/(4) x - 3

Hope this helps you

User Subin K Kuriakose
by
5.9k points